Destination Estimation for Bus Passengers Based on Data Fusion. (16th September 2020) - Liu, Wusheng; Tan, Qian; Liu, Lisheng
Abstract : The planning and operation of urban buses depend heavily on the time-varying origin-destination (OD) matrix for bus passengers. In most cities, however, only boarding information is recorded, while the alighting information is not available. This paper proposes a novel method to predict the destination of a single bus passenger based on bus smartcard data, metro smartcard data, and global positioning system (GPS) bus data. First, the attractiveness of each bus stop in a bus line was evaluated, considering the attractiveness of nearby metro stations. Then, the exploration and preferential return (EPR) model was employed to estimate the probability of a bus stop to be the alighting stop, i.e., the destination, of a passenger. The estimation result was obtained through a simulation based on the Monte Carlo (MC) algorithm. The effectiveness of our method was proved through a case study on the bus network in Shenzhen, China.